The effectiveness of electronic purchase on ordering national health insurance drugs at the West Bandung pharmacy of Indonesia - Agustini, Kamelia; Ratih Hurriyati; Vanessa Gaffar; Bella Tiana; Windi Novianti (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aimed to determine the flow of use of the electronic drug purchase application, the level of suitability for ordering drugs, the constraints through the electronic drug purchase application, and its effect on national health insurance drugs in Indonesia. We use a quantitative descriptive method to accompany pharmacists with the Guttman scale. The results showed that the flow of the use of electronic purchasing applications at the level of ordering drugs at pharmacies was in accordance with the e-catalog. The service level of 80.11% of the value of incoming goods receipts shows results that meet the criteria. Electronic purchases have been effective because the percentage of service level from the value of incoming goods receipts shows results that meet the criteria for conformity levels according to standards. This study provides input to the pharmacy in the use of electronic purchasing applications for procurement.